2015
DOI: 10.3857/roj.2015.33.4.294
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent chemoradiotherapy improves survival outcome in muscle-invasive bladder cancer

Abstract: PurposeTo evaluate survival rates and prognostic factors related to treatment outcomes after bladder preserving therapy including transurethral resection of bladder tumor, radiotherapy (RT) with or without concurrent chemotherapy in bladder cancer with a curative intent.Materials and MethodsWe retrospectively studied 50 bladder cancer patients treated with bladder-preserving therapy at Keimyung University Dongsan Medical Center from January 1999 to December 2010. Age ranged from 46 to 89 years (median, 71.5 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
1
10
0
1
Order By: Relevance
“…As some patients strongly prefer to retain their own bladders, interest in trimodal therapy (TMT), which combines transurethral resection (TUR) of bladder tumor with radiotherapy (RT), and chemotherapy, is increasingly considered as alternative therapy for MIBC. TMT is the most effective bladder-preserving treatment approach for MIBC [ 1 , 2 ]; however, to date, a prospective randomized trial directly comparing RC and TMT has not been conducted. Several studies showed that overall survival (OS) with TMT was similar to that achieved with RC [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…As some patients strongly prefer to retain their own bladders, interest in trimodal therapy (TMT), which combines transurethral resection (TUR) of bladder tumor with radiotherapy (RT), and chemotherapy, is increasingly considered as alternative therapy for MIBC. TMT is the most effective bladder-preserving treatment approach for MIBC [ 1 , 2 ]; however, to date, a prospective randomized trial directly comparing RC and TMT has not been conducted. Several studies showed that overall survival (OS) with TMT was similar to that achieved with RC [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…S.J. Byun et al ретроспективно изучили результаты органосохраняющего лечения 50 пациентов с мышечно-инвазивным РМП (средний возраст -71,5 года): пятилетняя общая выживаемость и раковоспецифическая выживаемость составили 37,2 и 30,2 % соответственно [20]. При многофакторном анализе индекс G оказался статистически значимым показателем прогноза, что позволило представить графическую зависимость (рис.…”
Section: возможности сохранения мочевого пузыря у больных пожилого воunclassified
“…Approximately 10% of non-invasive bladder cancer cases eventually progress to invasive cancer following the transurethral resection of the bladder tumor (3). Compared with non-invasive bladder cancer, patients with invasive disease have a poor prognosis, with a 5-year survival rate of 50% (4). Systemic chemotherapy remains the major therapeutic option for muscle-invasive bladder cancer in neoadjuvant and adjuvant settings, as well as for metastatic disease.…”
Section: Introductionmentioning
confidence: 99%